2021
DOI: 10.1038/s41467-021-23651-6
|View full text |Cite
|
Sign up to set email alerts
|

Citywide serosurveillance of the initial SARS-CoV-2 outbreak in San Francisco using electronic health records

Abstract: Serosurveillance provides a unique opportunity to quantify the proportion of the population that has been exposed to pathogens. Here, we developed and piloted Serosurveillance for Continuous, ActionabLe Epidemiologic Intelligence of Transmission (SCALE-IT), a platform through which we systematically tested remnant samples from routine blood draws in two major hospital networks in San Francisco for SARS-CoV-2 antibodies during the early months of the pandemic. Importantly, SCALE-IT allows for algorithmic sample… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…A number of included studies reported infection attack rates of SARS-CoV-2 among study participants: 29 studies measured positivity rates (i.e., current infection) [ 13 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], seven measured seroprevalence (i.e., prevalence of antibodies for SARS-CoV-2, indicating historic infection) [ 61 , 62 , 63 , 64 , 65 , 66 , 67 ], and four measured both positivity and seroprevalence rates [ 68 , 69 , 70 , 71 ]. Additionally, data regarding SARS-CoV-2 symptoms reported by study participants were provided by 32 articles [ 7 , 8 , 33 , 34 , 35 , 36 , 38 , 42 , 45 , 46 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of included studies reported infection attack rates of SARS-CoV-2 among study participants: 29 studies measured positivity rates (i.e., current infection) [ 13 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], seven measured seroprevalence (i.e., prevalence of antibodies for SARS-CoV-2, indicating historic infection) [ 61 , 62 , 63 , 64 , 65 , 66 , 67 ], and four measured both positivity and seroprevalence rates [ 68 , 69 , 70 , 71 ]. Additionally, data regarding SARS-CoV-2 symptoms reported by study participants were provided by 32 articles [ 7 , 8 , 33 , 34 , 35 , 36 , 38 , 42 , 45 , 46 , …”
Section: Resultsmentioning
confidence: 99%
“…A number of included studies reported infection attack rates of SARS-CoV-2 among study participants: 29 studies measured positivity rates (i.e., current infection) [13,, seven measured seroprevalence (i.e., prevalence of antibodies for SARS-CoV-2, indicating historic infection) [61][62][63][64][65][66][67], and four measured both positivity and seroprevalence rates [68][69][70][71]. Additionally, data regarding SARS-CoV-2 symptoms reported by study participants were provided by 32 articles [7,8,[33][34][35][36]38,42,[45][46][47][48][49][50][51][52][55][56][57][58]61,62,[68][69][70][72][73][74][75][76].…”
Section: Sars-cov-2 Infection and Morbiditymentioning
confidence: 99%
“…As part of an existing serological survey 14 , residual serum samples from routine blood draws from the University of California, San Francisco (UCSF) and San Francisco Department of Public Health (SFDPH) inpatient and outpatient healthcare systems were sampled between February 4 and February 17, 2021 (Supplementary Fig. 5 ).…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of the samples are illustrated in Table 1 . The full inclusion and exclusion criteria and sampling algorithm are described previously 14 . Briefly, we included patients undergoing routine blood testing, defined as blood chemistries and tests for sexually transmitted infections and rubella.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation